HUMAN-WILDLIFE CONFLICT IN INDIA: CAUSES, CONSEQUENCES, AND REMEDIES - A. S. Meshram; R. B. Meshram (ShodhKosh: Journal of Visual and Performing Arts, 2023)
Human-wildlife conflict (HWC) in India is a significant environmental and socio-economic challenge, fuelled by factors like habitat destruction, rising populations, and shifts in land use. This paper delves into the root causes, effects, and possible solutions for HWC in India, particularly focusing on conflicts involving species such as elephants, tigers, leopards, and crocodiles. It sheds light on the ecological, economic, and social repercussions of these conflicts and suggests a comprehensive approach to addressing them, which includes habitat restoration, engaging local communities, and leveraging technology. By examining various case studies and existing policies, the paper emphasizes the importance of integrated strategies that harmonize conservation efforts with the well-being of human populations.